Analisis Yuridis terhadap Peranan Bank Syariah dalam Kegiatan Perbankan di Indonesia - Wulanmas A.P.G. Frederik (Jurnal Hukum IUS QUIA IUSTUM, 2012)
The presence of Sharia banks offers customers with various banking products. It is just different from conventional banks in terms of pricing, both the selling price and the buying price. As for the types of products offered by Sharia banks are: Al-wadi’ah (savings), Financing with profit sharing, Bai’al- Murabahah, Bai’as-salam, Bai’Al-istihna, Al-Ijarah (Leasing), Al-Wakalah (Mandate), Al-Kafalah (warranty), Al-Hawalah, Ar-Rahn. The aim of this paper is: to find out the position of Sharia Banks in the Indonesian banking system, and to determine the role of Sharia Banks in the provision of banking services. The research method in this research is normative juridical approach. Based on the results and discussion of Sharia Bank position in the Indonesian banking system, the targets of Sharia banking development are: enhancing the benefits of Sharia banking for the public welfare; realizing a healthy, competitive, and efficient Sharia banking; assuring the compliance of Sharia principles consistently based on mudaraba (partnership); and assuring the precautionary principles. Furthermore, the role of Sharia Banks in the provision of banking services, which is based The Bank of Indonesia Regulation 6/ 17/PBI/2004 on Rural Banks based on Sharia principles and The Bank of Indonesia Regulation 6/24/PBI/2004 on Commercial Banks Conducting Business Based on Sharia Principles: Sharia Monitoring and Reporting Procedures for Monitoring Results to Sharia Supervisory Board.